Application of molecular genetic methods for birds (literature review) - Bagi, Zoltán; Kusza, Szilvia (Acta Agraria Debreceniensis, 2016)
Ornithology studies have been extended by molecular genetic techniques. In this paper we are dealing with the most common use of areas. Our basic aim is to give a comprehensive view of the most commonly used methods in ornithological studies, including the available results by their use. We also deal with the following areas: an essential step during examination namely the applicability of sample collecting methods, and the unique identification, also the sex determination, methodology of DNA barcoding, as well as the role of molecular methods to protect endangered species. We discussed the advantages and disadvantages of the methods, such as the current trend for each method.